The Relationship of Anxiety and Stress With Working Memory Performance in a Large Non-depressed Sample - Karolina M. Lukasik; Otto Waris; Anna Soveri; Minna Lehtonen; Matti Laine (FRONTIERS MEDIA SA, 2022)
Clinical anxiety and acute stress caused by major life events have well-documented detrimental effects on cognitive processes, such as working memory (WM). However, less is known about the relationships of state anxiety or everyday stress with WM performance in non-clinical populations. We investigated the associations between these two factors and three WM composites (verbal WM, visuospatial WM, and n-back updating performance) in a large online sample of non-depressed US American adults. We found a trend for a negative association between WM performance and anxiety, but not with stress. Thus, WM performance appears rather robust against normal variation in anxiety and everyday stress.